The Black-White Achievement Gap Revisited - Braun, Henry; Chapman, Lauren; Vezzu, Sailesh (Education Policy Analysis Archives, 2010)
This study examines trends in Black student achievement and in the Black-White achievement gap over the period 2000 to 2007, employing data from ten states drawn from the NAEP Grade 8 mathematics assessments. Results are obtained for three levels of aggregation: the state, school poverty stratum within the state, and schools within poverty stratum. In addition, information on the ten states’ education policies for the period 1998 to 2005 was compiled. States relative ranks on the overall strength of their reform efforts were compared to their relative ranks with respect to their success in improving Black student achievement and in reducing the Black- White achievement gap. This study constitutes an extension of earlier work that considered the same issues for the period 1992 to 2000 and, thus, offers a unique comparison between the pre-NCLB era and the present one. Although the ten states certainly differed in their outcomes, the general picture at all three levels of aggregation is quite clear: The achievement gaps are substantial and the introduction of federally mandated high stakes test-based accountability through No Child Left Behind has had a very modest impact on the rates of improvement for Black students and on the pace of reductions in the achievement gaps between Black students and White students. Moreover, there was only a weak association between states’ policy rankings and their rankings related to test results. It appears there is a need for both fresh thinking on education reform and a more concerted effort to collect comprehensive longitudinal information on states' education policies.